1996
DOI: 10.1136/bjo.80.8.732
|View full text |Cite
|
Sign up to set email alerts
|

Radiation related complications after ruthenium plaque radiotherapy of uveal melanoma.

Abstract: 2.7-13.8); for radiation maculopathy location of posterior tumour margin within 2 mm from the fovea (HR 3.4, 95% CI 2.0-6.0); and for radiation optic neuropathy location of tumour margin within 1 DD of the optic disc (RR 6.1, 95% CI 3.0-12.4). The 3 and 5 year probabilities of avoiding enucleation were 92% and 85%, respectively. Ten eyes were enucleatedsix because of recurrent tumour growth, three because of treatment complications, and one because of mistakenly suspected extraocular growth.Conclusion-The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
2
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(60 citation statements)
references
References 24 publications
4
53
2
1
Order By: Relevance
“…The 5-year probability for eye preservation was 72% compared to 82% in a French [37], 83% in a Swedish [15], and 85% in a Finish series [27]. The tumours were larger than in the French and Swedish but similar to the Finish series.…”
Section: Local Tumour Control and Eye Preservationmentioning
confidence: 68%
“…The 5-year probability for eye preservation was 72% compared to 82% in a French [37], 83% in a Swedish [15], and 85% in a Finish series [27]. The tumours were larger than in the French and Swedish but similar to the Finish series.…”
Section: Local Tumour Control and Eye Preservationmentioning
confidence: 68%
“…[31][32][33] Cataract extraction is feasible in these patients and can restore vision in some. [34][35][36] We found that panretinal photocoagulation can substantially reduce the severity of neovascular glaucoma and reduce the risk of enucleation by half (E.G., A.M.L., W.L., K.M.E., unpublished data, 2000).…”
Section: Commentmentioning
confidence: 99%
“…From our experience, doses exceeding 50-70 Gy used in these modalities may not be necessary (Tokuuye et al 1997). Radiation retinopathy is a frequent cause of visual acuity loss after ruthenium plaque radiotherapy (Summanen et al 1996), but in our patient, it occurred only in the limited area of the irradiated target, and as a result, his visual acuity was minimally affected. In patients treated with proton therapy, visual acuity evaluated at 3 years was preserved in twothirds of the patients, depending on the tumor size and location (Guyer et al 1992).…”
Section: Discussionmentioning
confidence: 59%